Quasi una fantasia: autobiographical milestones of Celso Furtado’s economic formation - Cardoso, José Luís (2021)
The article discusses the formation of Celso Furtado as a historian and economist of development and underdevelopment, highlighting the importance of autobiographical sources for the analysis of his thought and action. Following closely the trajectory of his Diários Intermitentes (Intermittent Diaries) (1937-2002), the article presents crucial moments of a journey marked by an active university life, participation in international organizations and political action at the service of different governments of Brazil. Special attention is given to his stays in international university environments (namely at the Universities of Paris, Cambridge and Yale), which punctuated his reflection on the issues of economic imbalance and social inequalities.